Design of steganography algorithm based on MPEG-4 coding scheme - YUAN Kai-guo; ZHANG Ru; XU Xin; NIU Xin-xin; YANG Yi-xian (Tongxin xuebao)
An information hiding algorithm based on MPEG-4 texture coding was proposed. Hiding information in VOP motion texture codes could be realized by replacing the YUV value of non-VOP pixels in the DCT coding block with secret data, and modifying the transparence of the VOP. It was proved by the experiment that the proposed algorithm has much better fidelity and capacity. The algorithm is highly desirable in the situations that high capacity information hiding in MPEG-4 video streaming.